Internalisasi Religiusitas Siswa Kelas V SD Melalui Kegiatan Membaca Asmaul Husna - Hamidah, Rifa Dwi; Markhamah, Markhamah (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
The habit of reading asmaul husna is one of the routine activities at SDN 1 Panusupan to instill religious values in students. This study aims to describe (1) the implementation of the teacher's method in the habit of reading Asmaul Husna and (2) the internalization of religious values in fifth grade students through habituation activities to read Asmaul Husna. The research method used is descriptive qualitative method with the type of case study research. Data collection techniques carried out include observation, interviews, and documentation. While the data analysis technique is carried out with the following steps: data collection, data reduction, data presentation, and drawing conclusions or verification. The research subjects were PAI teachers at SDN 1 Panusupan and fifth grade students at SDN 1 Panusupan. The results of the research found include, (a) the implementation of the teacher's method in the habit of reading Asmaul Husna, namely the classical method, individual method, and drill method and (b) internalization of religious values through the habit of reading Asmaul Husna is in the form of instilling the learning of faith and morals so as to develop students' personalities who have good personalities, have the potential for piety, and emotional intelligence.Â Â